Comparison of early radiological predictors of outcome in patients with colorectal cancer with unresectable hepatic metastases treated with bevacizumab. Issue 6 (30th October 2017) - Mazard, Thibault; Boonsirikamchai, Piyaporn; Overman, Michael J; Asran, Mohamed A; Choi, Haesun; Herron, Delise; Eng, Cathy; Maru, Dipen M; Ychou, Marc; Vauthey, Jean-Nicolas; Loyer, Evelyne M; Kopetz, Scott
Abstract : Objective: The purpose was to validate the prognostic value of an early optimal morphological response on CT in patients treated with bevacizumab-containing chemotherapy for unresectable colorectal cancer liver metastases (CLM). It also evaluated the prognostic value of size-based criteria and the association of optimal morphological response with the receipt of bevacizumab. Design: 141 patients treated first using bevacizumab and 142 patients from a randomised study evaluating the addition of bevacizumab to oxaliplatin-based chemotherapy were retrospectively analysed. Radiologists evaluated pretreatment and restaging CT scans using morphological response criteria. Responses were also assessed with size-based criteria: Response Evaluation Criteria in Solid Tumors (RECIST), early tumour shrinkage (ETS) and deepness of response (DpR). The ability of each criterion to predict progression-free survival (PFS), overall survival (OS) and postprogression survival (PPS) was determined using a univariate Cox proportional hazards model. Results: In both populations, median PFS was significantly longer for patients achieving an optimal morphological response (10.4 vs 6.8 months, p=0.03; and 8.3 vs 4.9 months, p<00001, respectively). Neither RECIST nor ETS responses were associated with a prolonged PFS. Median OS was longer for those with an optimal morphological response but only at second restaging in the first population (n=141, 20.8 vs 12.3 months, p=0.002). DpR but not optimal morphological response was associated with PPS. In the randomised study, an optimal morphological response was 6.2 times more likely among patients receiving bevacizumab (p<0.0001). Conclusion: In patients with unresectable CLM, early morphological response may be a better predictor of PFS than size-based response. The addition of bevacizumab improves morphological response rate.